2020
DOI: 10.1111/all.14307
|View full text |Cite
|
Sign up to set email alerts
|

Integrated mRNA and microRNA transcriptome profiling during differentiation of human nasal polyp epithelium reveals an altered ciliogenesis

Abstract: Background: Human adult basal stem/progenitor cells (BSCs) obtained from chronic rhinosinusitis with nasal polyps (CRSwNP) when differentiated in an air-liquid interface (ALI) usually provide a pseudostratified airway epithelium with similar abnormalities than original in vivo phenotype. However, the intrinsic mechanisms regulating this complex process are not well defined and their understanding could offer potential new therapies for CRSwNP (incurable disease). Methods: We performed a transcriptome-wide anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…The importance of miRNA regulation in the pathogenesis of the aforementioned allergic diseases is supported by many studies, but also in other allergic diseases such as food allergy or chronic rhinosinusitis the evidence for a role of miRNAs is emerging. 4,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Figure 2 provides an overview of miRNAs in cells and tissues that are associated with allergic diseases presented herein.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of miRNA regulation in the pathogenesis of the aforementioned allergic diseases is supported by many studies, but also in other allergic diseases such as food allergy or chronic rhinosinusitis the evidence for a role of miRNAs is emerging. 4,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Figure 2 provides an overview of miRNAs in cells and tissues that are associated with allergic diseases presented herein.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, other families were differentially represented, such as miR‐378, miR‐449, and miR‐548. Interestingly, miRNAs belonging to the miR ‐ 449 families are crucial to trigger multi‐ciliogenesis by suppressing cell cycle genes and the Notch pathway in the surface of some vertebrate epithelia 69 . On day 28, we found that the miRNA families similarly represented in CRSwNP and in the control group were miR‐17, miR‐188, miR‐449, miR‐548, and miR‐8.…”
Section: Mirnas In Crsmentioning
confidence: 80%
“…We demonstrated for the first time that the genetic transcriptional program responsible for ciliogenesis and cilia function is significantly impaired in CRSwNP epithelium respect to normal epithelium. We suggest that this alteration is due to a different expression profile of miRNAs, particularly of those belonging to mir‐34 and mir‐449 families 69 (Figure 3C).…”
Section: Mirnas In Crsmentioning
confidence: 99%
“…Ciliogenesis and cilia function are significantly impaired in the CRSwNPs epithelium, presumably due to the altered expression of miRNAs ( 30 ). The function of miRNAs in CRSwNPs remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-29b-3p can directly and indirectly regulate MMP-2 and MMP-9 expression ( 28 , 29 ). A recent study showed that ciliogenesis and cilia function are significantly impaired in the CRSwNPs epithelium, presumably due to the altered expression of miRNAs ( 30 ). Zhang et al ( 31 ) found that overexpression of miR-30a-5p can attenuate the epithelial-mesenchymal transition by repressing CDK6 expression in nasal polyps ( 31 ).…”
Section: Introductionmentioning
confidence: 99%